"The Stigma is what you do": Examining the Relationship Between Occupational Stigma and Worker Outcomes in the Aged Care Context. (February 2023) - Manchha, Asmita V.; Way, Kïrsten A.; Thai, Michael; Tann, Ken
Negative social evaluations about aged-care work continue to discredit those who perform this type of work. Drawing on 'dirty work' literature from the field of management and stigma theory from the field of psychology, this study examines occupational stigma in the context of aged-care work and its relationship with negative outcomes for people who work in aged care. Findings from a path analysis revealed that aged-care workers (n = 185) who ascribe occupational taints and poor occupational conditions with aged-care work perceive aged-care work as being stigmatized, and in turn, are more likely to internalize this stigma. Through this process of perceiving and internalizing occupational stigma, aged-care workers experience greater psychological distress, job dissatisfaction, and turnover intentions. This research fills a void within the gerontology literature regarding the psychological processes underlying how occupational stigma may come to negatively impact this workforce. Findings offer practical implications for policy reform and managerial training.